Efficacy of Xuebijing injection on pulmonary ventilation improvement in acute pancreatitis: a systematic review and meta-analysis - Bin, Yuling; Peng, Rumei; Lee, Yaqian; Lee, Zhijie; Liu, Yang (Frontiers in Pharmacology, 2025)
BackgroundXuebijing injection (XBJI), as a Chinese patent medicine injection, consists of five botanical drugs for anti-inflammatory treatment. Acute pancreatitis (AP) is induced by localized inflammation, potentially resulting in multiple organ dysfunction syndromes, specifically including acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). Recent studies suggest that XBJI effective in alleviating potentially easing ALI and ARDS.ObjectiveWe illustrated the efficacy and safety of XBJI for pulmonary function of AP by conducting a systematic literature review and meta-analysis.MethodsWe conducted searches across eight databases, including PubMed, Embase, and the Cochrane Library, up to September 2024. Two independent investigators screened and selected the literature based on predefined inclusion and exclusion criteria, followed by data extraction. The quality of the selected studies was assessed using the Cochrane Collaboration’s Risk of Bias 2.0 tool. The data were then qualitatively analyzed and synthesized by using Review Manager software, in accordance with the PRISMA guidelines and the Cochrane Handbook.ConclusionThis study showed that using conventional therapy combined with XBJI might increase the oxygenation index, lower the respiratory rate, and improve APACHE II scores and inflammatory biomarkers. However, there is a high risk of bias and the quality of the included studies is low. More well-designed, large-sample, and high-quality trials are needed to be conducted in multiple centers.